A capital group within the meaning of competition protection regulations and other legal regulations. Selected cases - Bartosz Kozicki; Monika Bychowska; Norbert Malec (Nowoczesne Systemy Zarządzania, 2023)
The concept of a capital group is both, simple and complex. Taking into account the literal definition of this concept, we can agree with the thesis that a capital group is a simple situation when one entrepreneur having power over other entrepreneurs. However, if it is necessary to consider specific cases of staying in a capital group for the purposes of specific regulations, then due to the complexity of the analyzed facts, existing doctrine and case law, the status of staying in one capital group does not have to be unambiguous and obvious. In cases where staying in the capital group is not obvious due to the ambiguous rights of the parent company, it may be necessary to examine specific individual actions taken by the partners towards the alleged subsidiary in order to determine whether it is an actual subsidiary (stays in the analyzed capital group).